Filosofia y literatura clave de la cultura Hispanica . - Gonzalez, Angela Sierra, Torres, Juan Manuel Diaz, Fuentes, Jesus Luis Paradinas; et. al; Campos, L.M. Pino.; Hernandez, R. Fenrnandez (Madrid Fundacion Fernanco Rielo, 2006)
Papers from a conference hosted by the Fundacion Fernando Rielo and the Universidad de La laguna, March 15-19, 2004.
Keywords: Literature--Philosophy.